Analisis Potensi Desa dalam Pengembangan Ekowisata Spiritual Bayan Berkelanjutan Menuju Desa Berdaya - Alvin Juniawan; Lilik Hidayati; Pahmi Husain (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to analyze the village potential and formulate a sustainable Bayan spiritual ecotourism model as an accelerator for Bayan Village, Bayan District, North Lombok Regency, towards the status of Empowered Village. Bayan Village in North Lombok has unique potential in the form of the sacred site of the Bayan Beleq Ancient Mosque and the local wisdom of Wetu Telu, but this potential is threatened by the risk of commercialization and the lack of structured customary governance. The method used is action research with a participatory qualitative approach, through SWOT analysis, FGDs, and customary workshops involving the Customary Council, Pokdarwis, and BUMDes. The results of this service produce scientific findings that the educational ecotourism model is only sustainable if the absolute authority of the customary council is determined as the main control variable that limits zoning and commercial activities. Based on these findings, a Bayan spiritual-customary ecotourism model is formulated that clearly distinguishes the sacred core zone and the educational buffer zone. This community service activity also successfully increased the human resources capacity of the Tourism Awareness Group (Pokdarwis) through ethical storytelling training, which serves as a filtering mechanism for cultural values. The main output of this activity was a strategic roadmap integrated into the village planning document (RPJMDes), which serves as an operational guide for the development of Bayan Village towards an Empowered Village through the synergy of cultural preservation, social empowerment, and local economic empowerment.